Non-destructive testing of weld specimen using phased array ultrasonic procedures - Lim, Wen Xun (2017)
Welding is a widely-used process in the industry to join metals together. Many industries employ welding to join the metal structures or products but the welds may contain defects or flaws which may compromise the integrity of the joint. To assess the quality of the weld without affecting the structure, non-destructive testing (NDT) is used. There are different types of NDT such as liquid- penetrant, magnetic particle testing, eddy-current testing, radiography and ultrasonic. There are different types of ultrasonic NDT such as conventional A-scan, B-scan and C-scan and the newer technology being phased array and time of flight diffraction (TOFD). This paper will focus on the use of ultrasonic NDT on the weld and in particularly, phased array technology. The author will compare the results of phased array, A-scan and C-scan using the same set of weld specimens. The weld specimens are real intended defects produced in the weld meant for educational purposes. The defect types are root crack, centreline crack, porosity, slag inclusion, lack of side wall fusion, incomplete penetration in the middle of weld and incomplete penetration at the bottom of the weld. The author will analyse the ability of the phased array technology to locate the defects in welds. Since most of the weld defects are sub-surface which means that the defects cannot be seen from the outer surface of the specimens, a specimen with side drill holes is used to compare the accuracy of the 3 different ultrasound techniques. Phased array technology is increasingly being used in the industry and this is not surprising due to the advantages that it has over the conventional technology. The phased array data clearly helps determine the location of the defects due to its ability to provide visualisation as compared to the other conventional scans. This reduces the chances of operator error which is common for conventional A-scans. Also, due to a wider area of coverage, the inspection by phased array is more efficient and less time-consuming. Although, C-scan also provides more detailed information than the conventional A-scan, it is not portable. Phased array equipment is also made portable and suitable for on-site inspections. Therefore, the phased array technology is clearly better than the conventional A-scan and C-scan.